Reliability and Risk Evaluation of Wind Integrated Power Systems - Billinton, Roy.; Karki, Rajesh; Verma, Ajit Kumar; SpringerLink (Online service) (India : Springer India : Imprint: Springer, 2013)
With the introduction of various types of incentives for renewable sources based electricity generation, the world is witnessing the rapid growth in wind, solar, biomass and other renewable based generation. Unlike electricity generation schemes based on conventional energy sources, wind power systems suffer from the uncertainty of wind availability and variability of the wind speed. In this regard, this volume intends to bring out the original research work of researchers from academia and industry in understanding, quantifying and managing the risks associated with the uncertainty in wind variability in order to plan and operate a modern power system integrated with significant proportion of wind power generation with an acceptable level of reliability. The accurate prediction of wind speed variability is very important for operation of electric power system in secure and safe environment and will play a crucial role in defining the requirement of various types of services such as ancillary services in the power system. This may also affect the electricity market strategy of conventional resources based power producers in the power market.
Determining Capacity Credit for Wind Used in MISO Resource Adequacy -- Wind Power Scenario Tree Tool: Development and Methodology -- Probabilistic Ramp Detection and Forecasting for Wind Power Prediction -- Application of Hourly Time Series Models in Day Ahead Wind Power Commitment -- Probabilistic Guarantees for the N-1 Security of Systems with Wind Power Generation -- Adequacy and Security Measures in Integrated Intermittent Renewable Generation -- Representation of Wind and Load Correlation in Non-Sequential Monte Carlo Reliability Evaluation -- Composite Reliability Assessment of Power Systems with Large Penetration of Renewable Sources.
Keywords: Economics; System safety; Renewable energy sources; Engineering economy; Environmental economics; Economics/Management Science; Environmental Economics; Quality Control, Reliability, Safety and Risk; Renewable and Green Energy; Energy Harvesting; Energy Economics